A member of the glycoside hydrolase family 76 is involved in growth, conidiation, and virulence in rice blast fungus. (January 2021) - Pan, Song; Tang, Liu; Pan, Xiao; Qi, Linlu; Yang, Jun
Abstract: Glycoside hydrolase family 76 (GH76) proteins with their endo-α-1, 6-mannanases domains are required for cell wall biogenesis in several model fungi, including Saccharomyces cerevisiae, Candida albicans, and Neurospora crassa . However, biological roles of GH76 proteins in phytopathogenic fungi remain unknown. The genome of the rice blast fungus Pyricularia oryzae contains seven GH76 protein-encoding genes. In this study, we functionally characterized one of them, PoGH 76-1, which is highly expressed in conidia. The deletion of PoGH 76-1 led to severe defects in colony growth and conidiation. Conidia produced by the PoGH 76-1 knockout mutant were mostly one- and two-celled. Deletion of PoGH 76-1 also resulted in impaired appressorium maturation, appressorial penetration, and attenuated virulence on rice leaves. Taken together, our findings suggest that PoGH 76-1 functions as an important determinant of fungal growth, development, and virulence in P. oryzae . Highlights: PoGH76-1 is an orthologous protein of Neurospora crassa Dcw1. PoGH76-1 is important to vegetative hyphal growth, conidiogenesis, and conidium morphogenesis. PoGH76-1 plays a key role in appressorium maturation, appressorial penetration, and virulence in  Pyricularia oryzae .